Rhetorical Moves in Broadcast Disaster News: A Corpus-Assisted Genre Analysis - Ismail, Mohamad Arif; Zakiyah, Fitriyatuz (International Journal of English and Applied Linguistics (IJEAL), 2026)
Growing scholarly attention to media discourse has stimulated increasing interest in the rhetorical organization of news texts. However, much of this research has focused on print journalism, leaving the structural dynamics of broadcast news, particularly disaster reporting, relatively underexplored despite its crucial role in communicating urgent information to the public. This study examines how disaster-related events are rhetorically structured and linguistically realized in broadcast television news. Drawing on a corpus of 23 disaster news reports produced by TVRI Sulawesi Tengah between 2024 and 2026, the study employs a corpus-assisted genre analysis to investigate the move structure and linguistic patterns that shape disaster news discourse. Using Hajimia et al.’s (2022) nine-move framework, the analysis first identifies the rhetorical moves that organize the reports and examines their distribution across the corpus. It then explores recurring linguistic patterns using AntConc to illustrate how these rhetorical functions are realized in the texts. The findings reveal that broadcast disaster news follows a relatively stable rhetorical structure centered on introducing the disaster event and elaborating its impacts and response actions. Move 1 (Title), Move 2 (Introducing the news lead), and Move 4 (Elaborating the event) emerge as the most obligatory components, while Submove 4b (Stating factual information) forms the core narrative element. These findings contribute to genre studies of media discourse and offer insights for journalism-related language instruction.